2021
DOI: 10.1002/qua.26649
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the helium atom embedded in classical nonideal plasmas

Abstract: Properties of the ground state of the helium atom embedded in classical nonideal plasmas have been investigated within the framework of variational method. The background plasma is described by a pseudopotential which has been deduced from the sequential solution of Bogolyubov's hierarchy equations. An extensive trial wave function is employed in Rayleigh-Ritz variational principle to compute various quantities associated with the ground state of helium atom quite accurately. A detailed study is made on the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In recent years, a number of theoretical investigations have been carried out to explore the effects of NI of the classical plasmas on the structural and collisional behaviour of atomic systems. [5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In the present work, we focus on the doubly excited singlet S ( 1 S e ) states in the helium atom (He) embedded in CNIP. Doubly excited states (DES) play a key role in the structural and collisional behaviours of an atomic system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of theoretical investigations have been carried out to explore the effects of NI of the classical plasmas on the structural and collisional behaviour of atomic systems. [5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In the present work, we focus on the doubly excited singlet S ( 1 S e ) states in the helium atom (He) embedded in CNIP. Doubly excited states (DES) play a key role in the structural and collisional behaviours of an atomic system.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, high‐density quantum plasmas and nonideal classical plasmas with low temperature and high‐density are important. [ 61 ] Furthermore, the obvious and sensitive effects of the endohedral cage on photoionization are interesting as well as the interaction with different confinement effects. Within this motivation, H@Cn${\text{H@C}}_{n}$ implanted in the NCP is taken into consideration, which is a first in the relevant literature to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Das and Ghoshal [6] also worked on the stability of the hydrogen molecular ion (H + 2 ), the stability of the negative hydrogen ion (H − ) [7], the properties and stability of the positronium negative ion [8] and the photodetachment cross section of the negative hydrogen ion (H − ) [9] in the presence of plasma non-ideality. Also, they [10] adopted the variational method to study the properties of the ground state of helium atoms and concluded that the 1 S state of He is stable in NICP for temperatures lying between (1-10) ×10 4 K and plasme density in the range 2.7 × (10 23 -10 26 ) m −3 . Das et al [11] executed a detailed study of single, double, and total photoionization of helium atoms for such a case taking into account high photon energies and employing a dipole approximation in the nonrelativistic regime.…”
Section: Introductionmentioning
confidence: 99%